Concentration and purification of citric acid using electrodialysis [microfilm] - Chew, Boon Chong (Skudai : Universiti Teknologi Malaysia, 2001)
Thesis (Master of Engineering (Chemical)) - Universiti Teknologi Malaysia, 2001